2012
DOI: 10.3168/jds.2011-5223
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes of bovine milk fat globules during in vitro digestion

Abstract: An in vitro digestion model that simulated gastric and intestinal fasting conditions was used to monitor the physical, chemical, and structural changes of fat globules from raw bovine milk. During in vitro gastric digestion, the fat globules were stable under low-acidic conditions. Some peptides and β-lactoglobulin were resistant to proteolysis by pepsin. Phospholipids, proteins, and peptides stabilized the globules in the stomach model. During in vitro intestinal digestion, most of the β-lactoglobulin and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
104
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(117 citation statements)
references
References 42 publications
(56 reference statements)
12
104
1
Order By: Relevance
“…The lower chain polypeptides and peptides formed during the digestion process will still be surface-active and are adsorbed at the interface of fat particles in the absence of lipase that would have affected the behavior of fat particles. Similar results were also reported by Li, Ye, Lee, and Singh (2013), Gallier, Ye, & Singh (2012) and who showed that the fat globule membrane was stable during proteolysis in the stomach. They also postulated that peptides generated by any proteolysis of membrane proteins will be adsorbed into the fat globule membrane, preventing the coalescence of fat globules.…”
Section: Microstructural Changessupporting
confidence: 91%
See 3 more Smart Citations
“…The lower chain polypeptides and peptides formed during the digestion process will still be surface-active and are adsorbed at the interface of fat particles in the absence of lipase that would have affected the behavior of fat particles. Similar results were also reported by Li, Ye, Lee, and Singh (2013), Gallier, Ye, & Singh (2012) and who showed that the fat globule membrane was stable during proteolysis in the stomach. They also postulated that peptides generated by any proteolysis of membrane proteins will be adsorbed into the fat globule membrane, preventing the coalescence of fat globules.…”
Section: Microstructural Changessupporting
confidence: 91%
“…After rehydration in water, vegetable oil (4.0 g/100 mL) and lactose (6.5 g/100 mL) were mixed uniformly using Silverson at 5000 rpm (Multimix) immediately before transfer to homogenizer at 5/25 MPa (Twin Panda 400, GEA). The liquid formulae was kept at 4 o C for a maximum two days with the addition of sodium azide (0.02% w/v) (Gallier, Ye, and Singh, 2012).…”
Section: Preparation Of Infant Milk Formulaementioning
confidence: 99%
See 2 more Smart Citations
“…These characteristics differ among milks (e.g. HM and bovine milk) and are modified after milk technological treatments (heat treatments, homogenization) (Innis et al, 2010;Gallier et al, 2012Gallier et al, , 2013aGallier et al, , 2013bGarcia et al, 2014;Bourlieu et al, 2015b;Le Huërou-Luron et al, 2016). Designing IF that mimic HM digestive behaviour supposes prior characterization of this behaviour.…”
Section: Introductionmentioning
confidence: 99%